Integration of SERVQUAL and Six Sigma for enhancing academic service quality in departments and laboratories: A case study - Ulfah, Maria; Arina, Faula; Sonda, Atia; Muharni, Yusraini; Anggraeni, Shanti Kirana; Gunawan, Akbar; S. Muttaqin, Ade Irman (Journal Industrial Servicess, 2025)
Academic services are super important for shaping how students experience their education and feel about their school. The quality of these services, whether in academic departments or laboratories, affects how well students perform, how engaged they are, and what they think of their institution. This study sets out to figure out the lowest gap value, calculate the sigma value and satisfaction level, and suggest ways to improve the academic services in the Department and Laboratory. We used Servqual and Six Sigma methods to dig into this. The results showed that all service attributes, for both the department and the lab, had negative gap values. For department services, the total sigma value was 2.205 with an average satisfaction level of 76.2%. For lab services, it was a sigma of 2.274 and a satisfaction level of 78.04%. The biggest issue for both was the same: the comfort of the study room in the department and the practicum room in the lab, which were rated as super important but had the lowest satisfaction. Using the 5W + 1H method, we came up with practical suggestions to fix what’s making students unhappy.